Challenges and Opportunities Implementation of Online Learning in the Pandemic Era - Na'imah, Na'imah; Hasan, Diqqi Alvin; Faizah, Nur; Rifathi, Fina Umu; Abqori, Muhammad Sabiq (Mahesa Research Center, 2022)
The World Health Organization (WHO) stated that COVID-19 was a pandemic that has spread worldwide. It has been on limited interaction activities and social group meetings. The policy of limiting community physical interaction directly affects the education sector so that the learning process is fully transformed into the form of online learning. The purpose of this research is to find out the challenges and opportunities in the online learning process that has been implemented during the covid-19 pandemic. This study uses a descriptive qualitative research method by describing the online learning process that has been implemented. The subjects in the study were students and teachers of Junior High School 01 Plantungan Kendal. Analysis of the data used in this study is to triangulate data consisting of data from observations, interviews, and field observations. The study's results showed that the online learning process had challenges regarding the availability of qualified technology such as electronic devices in the learning process, internet networks, and students' and teachers' readiness to face online learning. While the opportunities from the online learning process that have been implemented are directly familiarizing students to practice independently in the learning process, and from the teacher's side, encouraging teachers to master technology and innovate in the learning process so that it would be more varied and effective